A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 4 years ago
Solve using mathematical induction: 1+2+3+4.....n=n(n+1)/2
anonymous
 4 years ago
Solve using mathematical induction: 1+2+3+4.....n=n(n+1)/2

This Question is Closed

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0let n = k sum k terms = k(k+1)/2 (k+1)th term = k+1 so sum k+ 1 terms = k(k+1)/2 + k+1 = [k(k+1) + 2(k+1)] / 2 = (k+1)(k+2) / 2 this is the sum of k terms where k is replaced by k + 1 therefore if the sum to k terms is correct then sum to k+1 terms is correct the sum of 1 term = 1*2 / 2 = 1 which is correct so it must be true for 2,3,4 .... terms thus the formula is true for n terms (any number of terms)
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.